SINTESIS 4–HIDROKSI–3–KLOROBENZALDEHID DARI p–HIDROKSIBENZALDEHID DAN GAS Cl2 - Warsi Warsi (Pharmaciana, 2015)
Curcumin is a compound which potential to be developed. The curcumin analogues havebeen synthesized. The compound 3–chloro–4–hydroxybenzaldehyde was used as starting material inthe synthesis of curcumin analogues with Cl substituent on the aromatic ring. The compound of3–chloro–4–hydroxybenzaldehyde were synthesized by chlorination reaction betweenp–hydroxybenzaldehyde and Cl2 gas. The purity of 3–chloro–4–hydroxybenzaldehyde wasdetermined base on the melting range, thin layer chromatography and LC–MS. The structureidentification of the compound was observed done by spectrometry techniques, including massspectra (ESI–MS), infrared spectra (cm-1, KBr), Nuclear Magnetic resonance proton spectra (δ, ppm,DMSO-d6, 1H–NMR, 500 MHz) and UV–Vis spectra. Chlorination reaction ofp–hydroxybenzaldehyde produced yellow crystal of 3–chloro–4–hydroxybenzaldehyde, its meltingrange is 128.1 to 130.8ºC. The average yield obtained of this reseach is 51.37%.